The Development of Oral and Written Speech is the Main Factor in the Versatile Development of Students and the Full Realization of Their Capabilities (Journal of Pedagogical Inventions and Practices, 2022)
The article discusses the development of oral and written speech as the main factor shaping personality, the fundamental differences between the main types of oral and written speech. Psychological and methodological aspects of writing formation are presented.